Methodology to evaluate the Quality of Public Services - Catalin Popescu; Tatiana Cucu; Luminita Ion-Boussier; Jean-Marie Boussier; Augustin Mitu (Amfiteatru Economic Journal, 2009)
The preferences of citizens and their satisfaction level for the actions carried out in the public sectors are usually established by questionnaires, taking into account the specificities and priorities of each city. No global methodology exists to collect and to treat information because of various variables to be tested, upgradeable character of the human behaviour and his subjective perception. We propose a global methodology that will join two methods. With the method of fractional array to obtain a very low number of questions, we can pattern the relationship between the tested variables (price, security, etc.) and the characteristic of the wanted performance (such as the quality of the service). Interviewed people can be classified into socio-demographic categories by the tool user. Afterwards, the Analysis of Variance gives significant variables. A reduced model illustrating a “mean” behaviour is designed for all hypothetical situations. The proposed methodology is tested for the category “student” in two case studies: to evaluate the teaching quality at Faculty of Economic Sciences (FSE) within Oil and Gas University from Ploiesti (Romania) and to estimate the quality of using car parks in La Rochelle (France).
Keywords: L80; N7; C60; I21; I23; C12; R41; 330; fractional array; students' evaluation; behavioural model; road users